High-throughput screening identifies compounds that protect RPE cells from physiological stressors present in AMD. (August 2019) - Cai, Hui; Gong, Jie; Abriola, Laura; Hoyer, Denton; NYSCF Global Stem Cell Array Team,; Noggle, Scott; Paull, Daniel; Del Priore, Lucian V.; Fields, Mark A.
Abstract: Dysfunction and eventual loss of retinal pigment epithelial (RPE) cells is a hallmark of atrophic age-related macular degeneration (AMD), and linked to oxidative and nitrosative damage. Herein, we use a high-throughput screen (HTS) to identify compounds that protect human RPE cells from oxidative stress-induced cell death and elucidate the possible mechanism of action. HTS was used to identify compounds that protect RPE cells from oxidative damage. We tested the identified compound(s) in models of RPE stress, including tert -butyl hydroperoxide (TBHP) exposure, ultraviolet-B (UV-B)-mediated light damage and nitrosative stress to the basement membrane using ARPE-19 cells, primary human RPE cells and induced-pluripotent stem cell (iPSC)-derived RPE cells from patients with AMD. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to detect gene expression of oxidative stress- and apoptosis-related genes and mitochondrial function was measured using a Seahorse XF96 analyzer to elucidate possible mechanisms of action. Five thousand and sixty-five compounds were screened, and of these, 12 compounds were active based on their ability to improve cell viability after exposure to TBHP. After chemical structure review, we identified ciclopirox olamine as a potent inhibitor of oxidative damage to RPE cells. Ciclopirox olamine increased cell viability in ARPE-19 cells treated with TBHP, UV-B light or on nitrite-modified extracellular matrix (ECM) by 1.68-fold, 1.54-fold and 4.3-fold, respectively (p < 0.01). Treatment with TBHP altered expression of genes related to oxidative stress and apoptosis, which was reversed by pretreatment with ciclopirox olamine. Ciclopirox olamine improved mitochondrial function in TBHP-exposed ARPE-19 cells and iPSC-derived RPE cells. Ciclopirox olamine protected primary human RPE cells and iPSC-derived RPE cells from the oxidative stress or damaged basement membrane. HTS of bioactive Food and Drug Administration (FDA)-approved libraries and follow-up studies can be used to identify small molecules (including ciclopirox olamine) that protect RPE cells exposed to various stressors associated with disease progression of AMD. This strategy can be used to identify potential compounds for treatment and prevention of AMD. Highlights: A high-throughput screen (HTS) was developed to identify compounds that protect human RPE cells from oxidative damage. Ciclopirox olamine protects RPE cells from oxidative damage and nitrosative damage to the basement membrane. This HTS protocol can be used to identify potential compounds that may prevent or delay the progression of atrophic AMD.